Implementasi Metode WASPAS Pada Sistem Pendukung Keputusan Penilaian Kinerja Perawat Terbaik - Pratama, Arya Yendri; Muttakin, Fitriani; Permana, Inggih; Zarnelly, Zarnelly; Marsal, Arif (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Hospitals are health service institutions that provide various services to the community, including inpatient, outpatient and emergency care. Hospitals as health service institutions require optimal nurse performance in providing quality services to patients. At XYZ Hospital, assessments and calculations are still carried out manually, often experiencing difficulties because in carrying out the assessment all the calculation data is carried out one by one, resulting in large errors and taking quite a long time to obtain the decision results and it is difficult to carry out rankings due to frequent assessment forms. scattered. There are 14 criteria for assessing nurse performance, namely loyalty/loyalty, work performance, responsibility, obedience/discipline, honesty, cooperation, communication, knowledge, competency I nurse (PK I), competency II nurse (PK II), competency III nurse (PK III), the presence of hand washing in the room, the quality of the work carried out by the person concerned, and the availability of ready-to-use facilities & infrastructure for the next shift. To obtain accurate performance assessment results, a decision support system was created using the WASPAS method. The WASPAS method is said to be appropriate for selecting the best nurses because it is ranked based on specified criteria values. It is hoped that the research carried out will help obtain effective results. In this research, the results obtained were that the best nurse at XYZ Hospital was the alternative with a score of 50,038 in the name of EET.